2021
DOI: 10.1080/11956860.2021.1907974
|View full text |Cite
|
Sign up to set email alerts
|

Vascular plant communities in the polar desert of Alert (Ellesmere Island, Canada): Establishment of a baseline reference for the 21st century

Abstract: The startling warming of the Arctic is driving important environmental changes, but vegetation responses have been spatially heterogeneous and difficult to predict. In this context, establishing new ecological baselines and initiating monitoring schemes are essential. We conducted systematic plot-based surveys in the polar desert surrounding Alert (Nunavut, Canada). We aimed at (1) identifying distinct plant communities, (2) characterizing community attributes, including diversity and abundance, as well as env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 97 publications
(137 reference statements)
1
6
0
Order By: Relevance
“…For example, the forb-dominated barren, the driest vegetation class, had the furthest mean distance from a snowbank (Table S2). In addition, we found that distance to snowbanks emerged as the most important predictor of sedge-dominated wetland, thus confirming Desjardins et al [75], who had demonstrated at the same site an association between this community and perennial snowbanks. To our knowledge, snowbanks were never previously used as a predictor of vegetation classification in the Arctic.…”
Section: Predictor Importancesupporting
confidence: 91%
See 2 more Smart Citations
“…For example, the forb-dominated barren, the driest vegetation class, had the furthest mean distance from a snowbank (Table S2). In addition, we found that distance to snowbanks emerged as the most important predictor of sedge-dominated wetland, thus confirming Desjardins et al [75], who had demonstrated at the same site an association between this community and perennial snowbanks. To our knowledge, snowbanks were never previously used as a predictor of vegetation classification in the Arctic.…”
Section: Predictor Importancesupporting
confidence: 91%
“…We obtained ground references for seven land cover classes: forb-dominated barren, forb-dominated tundra, grass-dominated wetland, sedge-dominated wetland, mossdominated wetland, water, and snow. The five plant communities were identified in Desjardins et al [75] and are described in Table 1. Briefly, we conducted stratified random plot-based surveys during the summers of 2018 and 2019, with survey locations adjusted so that plots were located within homogeneous vegetation patches.…”
Section: Data Acquisition and Extraction 221 Ground Reference Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The region is part of the polar desert biome (Bliss 2000 ). Plant communities mostly consist of herbaceous and low shrub species, mosses, and lichens (Desjardins et al 2021a , 2021b ; Government of Canada 2018 ). The area surrounding CFS Alert is rugged with hills, small lakes, and ponds.…”
Section: Methodsmentioning
confidence: 99%
“…[ 29 ]. IndVal assesses the strength of the association between a single species and several groups of relevés, each group representing a plant community [ 30 ], and is given by the indicator species analysis [ 24 ].…”
Section: Methodsmentioning
confidence: 99%